Seroprevalence OF Antibodies against SARS-COV2 - Iqbal, Mehveen (International Journal of Pathology, 2021)
Study Background: The novel corona virus (COVID -19) is a known virus in current pandemic. Clinical presentation ranges from asymptomatic to severe respiratory and multiple organ failure2.Large number of SARS-COV2 cases are documented as asymptomatic or with mild illness. To determine the extent of infection, serological evidence of SARS-COV2 antibodies is warrantedObjectives of the Study: To study the Seroprevalence of covid-19 antibodies among hospitalized patients and to determine the cumulative immunity in hospitalized patients.Methodology: This cross-sectional observational study was conducted at United hospital and Creek General Hospital, Karachi during the duration from December 2020 to February 2021. The study was approved by institutional ethical review board. Probability convenience method of sampling was used to collect blood samples. Patients of both genders having age group ranging from 1-80 years or above were included. These patients were asymptomatic and admitted due to non- COVID 19 reasons. Rapid test was used to detect SARS-COV2 IgM/IgG antibodies. Statistical analysis of data was performed by using SPSS-22. Age is organized into different subgroups. Chi-square test was applied to determine the significance between age groups and seropositive cases.Results: 800 blood samples were collected from different age groups of hospitalized patients and analyzed. 18.8% (n=151) cases were observed seropositive. 25.7% (n=61) seropositive cases were in age group 16-30 years followed by 19.5% in age group from 61-75 years. Statistical significant correlation was observed among seropositive IgG cases and age group ranging between 16-45 in female and above 45 in males.Conclusion: This study concluded 18.8% seroprevalence among asymptomatic admitted patients. The criteria of herd immunity is not fulfilled but it can be used for further research. The chance of seropositivity in females during reproductive age group is more as compared to other age groups.